2002
DOI: 10.1112/s0024610702003411
|View full text |Cite
|
Sign up to set email alerts
|

Strict Completely Positive Maps between Locally C * -Algebras and Representations on Hilbert Modules

Abstract: The structure of the continuous strict completely positive linear maps between locally C * -algebras is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…) which satisfy conditions (a)-(c) of (1) and there is a unitary operator U q in L B q (E [̺ q ], F q ) which satisfies conditions (i)-(iii) of (2). Moreover,…”
Section: By Step 1 There Is a Covariant Representation (φmentioning
confidence: 99%
See 1 more Smart Citation
“…) which satisfy conditions (a)-(c) of (1) and there is a unitary operator U q in L B q (E [̺ q ], F q ) which satisfies conditions (i)-(iii) of (2). Moreover,…”
Section: By Step 1 There Is a Covariant Representation (φmentioning
confidence: 99%
“…The proofs are not always straightforward. In [2], the author extended the KSGNS (Kasparov, Stinespring, Gel'fand, Naimark, Segal) construction to a strict continuous, completely positive linear map from a locally C * -algebra A to L B (E), the locally C * -algebra of all adjointable operators on a Hilbert module E over a locally C * -algebra B. A covariant version of this construction is proved in [5].…”
mentioning
confidence: 99%
“…They were first considered independently by A. Mallios in [7] and N. C. Phillips in [8], where the latter showed that most of the basic properties of Hilbert C * -modules are valid for Hilbert modules over locally C * -algebras. The Hilbert modules over locally C * -algebras are also studied in [4], [5] and elsewhere. Thus in [4] the present author proved a stabilization theorem for countably generated Hilbert modules over locally C * -algebras and in [5] she proved a version of the classical KSGNS (Kasparov, Stinespring, Gel'fand, Segal, Naimark) construction in the context of Hilbert modules over locally C * -algebras.…”
Section: Introductionmentioning
confidence: 99%
“…The Hilbert modules over locally C * -algebras are also studied in [4], [5] and elsewhere. Thus in [4] the present author proved a stabilization theorem for countably generated Hilbert modules over locally C * -algebras and in [5] she proved a version of the classical KSGNS (Kasparov, Stinespring, Gel'fand, Segal, Naimark) construction in the context of Hilbert modules over locally C * -algebras.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatt and Karia [2] gave the Stinespring's construction for locally C * -algebras and Joiţa [10] generalized the KSGNS construction in the context of Hilbert modules over locally C * -algebras. Let p be any element in S(A).…”
Section: Ksgns Type Constructions For α-Cp Maps On Locally C * -Algebramentioning
confidence: 99%